Conflict Management in the Enforcement of Regional Regulations by the Civil Service Police Unit of Sumenep Regency - Zamzami Sabiq; Siti Mujanah; Achmad Yanu Alif Alif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research explores the conflict resolution methods employed by the Civil Service Police Unit (Satpol PP) in Sumenep Regency in the context of enforcing regional regulations, with a particular focus on the displacement of street vendors (PKL). The implementation of these regulations frequently leads to social tensions, especially when they impact marginalized groups like street vendors. Using a qualitative case study method, the study was carried out in urban parts of Sumenep, including Taman Tajamara and Giling Sumenep. Data were gathered through comprehensive interviews, on-site observations, and document analysis. The results indicate that coercive enforcement measures often provoke stronger public opposition, whereas approaches that encourage cooperation and community involvement are more successful in fostering mutual trust and resolving disputes peacefully. The research highlights the necessity of embedding social justice values and restorative approaches in regulatory enforcement to promote constructive and harmonious relationships between authorities and the public.